ChemInform Abstract: Anionic Ordering and Thermal Properties of FeF3·3H2O. Issue 49 (December 2015) - Burbano, Mario; Duttine, Mathieu; Borkiewicz, Olaf; Wattiaux, Alain; Demourgues, Alain; Salanne, Mathieu; Groult, Henri; Dambournet, Damien
Abstract: In view of the potential use of FeF3 ·0.33H2 O with the hexagonal tungsten bronze (HTB) structure as cathode material for batteries from steel industry pickling sludge, β‐FeF3 ·3H2 O is prepared by precipitation from an aqueous solution of Fe(NO3 )3 and HF in a 1:4 molar ratio supported by microwave heating (90 °C, 30 min) and followed by cooling and vacuum solvent extraction (85% yield).